PERAN SISTEM INFORMASI MANAJEMEN DALAM PENGELOLAAN ADMINISTRASI PEGAWAI DI BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI UTARA - Bororing, Ribkah Christine; Tulusan, Femmy; Tampi, Gustaf Budi (Sam Ratulangi University, 2016)
Abstract: In the present era of government began to implement the e-government program. Thelast few years the government has been utilizing technological advances in various activities,including the public service based on information technology gained recognition. RegionalPersonnel Agency (BKD) North Sulawesi Province. The agency is an agency that already usepersonnel information system to process data and information and decision-making for specificsituations such as a promotion, a raise, a shift or mutation, and other relevant rules. Data andinformation is confidential and prudence. The method used in this research is qualitative research.Then, for the data used consist of primary data and secondary data. With the technique ofcollecting data through observation, interviews, and documentation. Data obtained from varioussources and has analyzed, with several stages of data reduction, data presentation, andconclusion. Researchers infer from each corner of the data and information administration,employment applications, employee capability, equipment for the system, every administrativeprocedure. Researchers conclude that the management information system has been running welland answer the problem formulation management information system is a collection of elementsthat are interconnected with each other to form a single unit to integrate data, process and storeand distribute information. At the Regional Employment Board of North Sulawesi these elements isthe data and information of employees, employment applications, employee, equipment for thesystems, and procedures for the administration. These elements are intertwined to be able tomanage and deliver the results to the administration required.Keyword : System, Employee, SIMPEG, e-government.